Pengaruh Media Diorama Tiga Dimensi Terhadap Hasil Belajar Kognitif Materi Mengenal Penggunaan Uang Pada Mapel IPS Kelas III SDN Balong Bowo - Selly Effa Weranti (JICTE (Journal of Information and Computer Technology Education), 2017)
Based on the results of observation in learning, teachers are still seen to dominate the teaching and learning process. Students only receive information from teachers that can cause a lack of enthusiasm so that makes the learning atmosphere that takes place looks still passive. It resulted in student learning outcomes still have not reached the maximum because of the use of media applied by teachers not in learning. This research is Quantitative research with Quasi Experimental Form Designjenis Nonequivalent control group design. The data collection technique used is the test of cognitive learning outcomes. Based on the results of data analysis obtained: 1) there is the effect of three-dimensional diorama media on the cognitive learning outcomes of the material recognize the use of money in the class III IPS SDN Balong dowo. This is proven by doing the calculation to determine the gain value of the result of unknown gain experimental class III-B with the yield of 9.09% belong to the criteria "high", meaning there is a high influence on the media diorama of three dimensions in 2 students. 90.91% entered into the criterion "medium" means there is influence "moderate" to 20 students. 2) there is a big influence of three-dimensional diorama media on student learning outcomes class III with N-gain analysis Based on the calculation obtained experimental class III-B 0,56. So in this case the influence of three-dimensional diorama media on student learning outcomes class III SDN Balong dowo moderate category because the criteria 0,56 ≤ 0.70